Managing Digital Teams While Being a Mother: The Lived Experiences of Mompreneurs in Makassar - Tenri Sayu Puspitaningsih Dipoatmodjo; Abdul Halid Latif (Abadi Institute, 2023)
This study explores how mompreneurs in Makassar manage digital human resources while balancing their roles as mothers and business leaders. Using a qualitative phenomenological approach, in-depth interviews were conducted with 15–20 mompreneurs operating fully digital and hybrid businesses. The findings reveal that participants rely on adaptive and resource-efficient HRM practices rather than formal management systems. Two major themes emerged. First, digital and hybrid business models require different HRM strategies, with digital businesses emphasizing flexibility and project-based collaboration, while hybrid businesses demand greater coordination across physical and virtual teams. Second, managing dual identities creates persistent emotional tensions, as participants continuously negotiate the competing expectations of motherhood and leadership. Despite these challenges, mompreneurs demonstrate resilience through adaptive leadership, flexible boundary management, and the creative use of accessible digital technologies. This study extends digital HRM and women's entrepreneurship literature by illustrating how gender roles, resource constraints, and digital work intersect in micro-enterprises. The findings also provide practical insights for policymakers, digital platform developers, and entrepreneurship support programs seeking to strengthen gender-responsive digital entrepreneurship in emerging economies.